Brief Review: Virtual Reality and Physical Exercise as Countermeasures of Coping the Space Missions - Russomano , Thais; Vinagre , Nelson A. C.; Gessinger , Rosirene P; Castro , João de C; Herbert , Juliana da S; Oliveira , Alcyr; Oliveira , Edson; Costa , Kalanna L.G.; Xavier , Ana P; Ruiz , Robson; Dihl , Yann; Knechtle , Beat; et al. (Health Nexus, 2024)
Microgravity is an environment incompatible with human physiology that induces unique physiological changes to the body. Exposure to microgravity environment can cause some possible physiological hazards, such as impairment of immune function, bone mass and skeletal muscle mass, in addition to possible negative psycological alterations (depression, anxiety, apathy, and personality changes). These pysico-physiological changes negatively impact health status and quality of life and result in operational difficulties on a space mission for the astronauts. Countermeasures designed to lessen the effect of microgravity on the human body include daily physical exercise and rehabilitation, psychotherapy, specific diets, pharmaceutical treatments, and the use of technologies. Virtual reality (VR) added to physical exercise programs, in the training and preparation of the astronauts for the space missions, could have more exuberant effects. Therefore, the aim of this perspective article is to present the application of VR and physical exercise as countermeasures for training and preparation before, during and after a space missions.